Hepatoprotective and antioxidant effect of ellagitannins and galloyl esters isolated from Melaleuca styphelioides on carbon tetrachloride-induced hepatotoxicity in HepG2 cells. (1st September 2016) - Al-Sayed, Eman; Esmat, Ahmed
Abstract: Context In a previous study, the total extract of Melaleuca styphelioides Sm. (Myrtaceae) showed a significant hepatoprotective effect in a CCl4 -induced toxicity model in mice. However, the active components responsible for the activity of the extract were not identified. Objective To determine the in vitro hepatoprotective activity of the isolated pure compounds from M. styphelioides leaves using the CCl4 -challenged HepG2 cell model. Materials and methods The hepatoprotective activity of the compounds (at concentrations of 100, 50 and 25 μm), the total extract and silymarin (Sil) (100, 50 and 25 μg/ml) was determined by measuring the activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) after pretreatment with the tested samples for one hour. Glutathione (GSH) and superoxide dismutase activity (SOD) were estimated to determine the mechanisms of the hepatoprotective activity. Results Some compounds showed marked hepatoprotection, including tellimagrandin I, which produced 42, 36 and 31% decrease in ALT and 47, 43 and 37% decrease in AST, at the tested concentrations, respectively, pedunculagin (32, 32 and 30% decrease for ALT and 48, 48 and 45% for AST), tellimagrandin II (38, 32 and 26% decrease for ALT and 45, 40 and 34% for AST) and pentagalloyl glucose (30, 28 and 26% decrease for ALT and 45, 38 and 36% for AST). Tellimagrandin I and II showed the highest increase in GSH (113, 105 and 81% and 110, 103 and 79%, respectively), which was comparable to Sil. Pedunculagin produced the highest increase in SOD (497, 350 and 258%). Conclusion This study highlights promising natural hepatoprotective candidates derived from M. styphelioides .